1985
DOI: 10.1098/rspa.1985.0047
|View full text |Cite
|
Sign up to set email alerts
|

On the direct imaging of offretite, cancrinite, chabazite and other related ABC-6 zeolites and their intergrowths

Abstract: Zeolites that belong to the so-called ABC-6 family may be regarded as having been assembled architecturally from individual sheets, each of thickness ca . 2.6 Å (1 Å = 10 -10 m = 10 -1 nm). The sheets consist of macro-anions of corner-linked SiO 4- 4 and AlO 5- 4 tetrahedra (Si: Al ranging from 1- 4 ), charge-compensating cations, typically Na + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(4 citation statements)
references
References 23 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…In gmelinite, the D6R units are stacked in the sequence of ABAB instead of ABCABC [23]. Chabazitegmelinite intergrowths have been reported by several researchers [22,23,26,27], indicating that these two frameworks may share similarly structured nuclei. Moreover, Daniels et al [22] observed that with increase in the Si/Al ratio of the composition, chabazite is the preferred product.…”
Section: Film Versus Powder Compositionmentioning
confidence: 99%
“…In gmelinite, the D6R units are stacked in the sequence of ABAB instead of ABCABC [23]. Chabazitegmelinite intergrowths have been reported by several researchers [22,23,26,27], indicating that these two frameworks may share similarly structured nuclei. Moreover, Daniels et al [22] observed that with increase in the Si/Al ratio of the composition, chabazite is the preferred product.…”
Section: Film Versus Powder Compositionmentioning
confidence: 99%
“…Hierarchically porous zeolites can also be prepared without the employment of secondary hard or soft templates. Several methods including engineering of intergrowth, , additive-assisted crystallization, ,, seed-induced synthesis, , a controlled crystallization process, ,, and designing special structure-directing agents have been reported for the synthesis of hierarchically porous zeolites in the absence of organic templates.…”
Section: Synthesismentioning
confidence: 99%
“…In particular, these OSDAs favored the generation of ultrathin plates with perpendicularly rotational intergrowth, resulting in the formation of the hierarchically porous structure. The synthesis of hierarchical zeolite formed by the intergrowth of two zeolite crystal structures has been explored in other systems, such as FAU/EMT, EMT/FAU, ETS-4/ETS-10, CAN/SOD, MFI, and CHA . However, only the SPP morphology has been reported to contain zeolite nanosheets of single-unit-cell thickness …”
Section: Synthesismentioning
confidence: 99%
“…The presence of stacking faults may affect important zeolite properties and, hence, their performance in catalysis and separation applications. For instance, in the so-called ABC-6 family, disorder may result in pore blockage, and it may also alter the catalytic performance of the disordered material . The degree of intergrowth in MFI/MEL catalysts and membranes may impact their catalytic as well as their permeation and selectivity properties, respectively .…”
Section: Introductionmentioning
confidence: 99%